SPECIFICATIONS OF RABI OSCILLATIONS IN THE QUANTUM EMITTERS SYSTEMS COUPLED TO THE LOCALIZED PLASMON POLARITONS - Nerkararyan, S.Kh.; Babajanyan, A.Zh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In this work phenomenon of resonant transfer of the excited energy between quantum dipole emitters (QDE) by the localized plasmon polaritons (LPP) is investigated. In system the molecules or semiconductor quantum dots act as QDEs and the nanometer size metal particles (MNP) care LPPs. The dependence of the frequency of Rabi oscillations on system parameters (the distance between MNP and QDE, the radius of MNP and dielectric permittivity of the surrounding medium) was determined. Conditions when the period of Rabi oscillations is considerably shorter than system relaxation time were defined.
Keywords: quantum dipole emitter, quantum dot, metalnanoparticle, localized plasmon polaritons